Study of the roads of Galicia: A review of the historiography of the Roman roads of the last 150 years - Argüelles Álvarez, Patricia Ana; Villanueva Acuña, Manuel (REVISTA DE HISTORIOGRAFÍA (RevHisto), 2024)
This study proposes an analysis of the state of the art on research of the Roman road network at Galicia. The understanding of the classical sources together with the works published since the late nineteenth century, will allow us to gather an overview of how the evolution of this branch of research has been at the Hispanic level. We are interested in Roman Gallaecia, and especially in the modern Galicia. A singular interest will be devoted to the methodological processes and historiographical trends in the research of the road case.
Keywords: roads; historiography; Rome; Galicia